2008
DOI: 10.1136/jcp.2007.047324
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic dysregulation of the DAP kinase/p14/HDM2/p53/Apaf-1 apoptosis pathway in acute leukaemias

Abstract: Among AML subtypes, DAP kinase is preferentially hypermethylated in APL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
2

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 36 publications
2
10
0
2
Order By: Relevance
“…As for the AML patients, only one out of 12 cases displayed methylation in this gene. Chim et al (2008) and Christiansen et al (2003) reported absence of p14 methylation in AML patients, which was consistent with RNA expression studies (Schwaller et al, 1997). On the other hand, five CLL patients out of 20 showed methylation in p14.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…As for the AML patients, only one out of 12 cases displayed methylation in this gene. Chim et al (2008) and Christiansen et al (2003) reported absence of p14 methylation in AML patients, which was consistent with RNA expression studies (Schwaller et al, 1997). On the other hand, five CLL patients out of 20 showed methylation in p14.…”
Section: Discussionsupporting
confidence: 77%
“…Low frequency of DAPK methylation in AML was previously reported (Katzenellenbogen et al, 1999;Galm et al, 2005;Chim et al, 2008;Griffiths et al, 2010). In contrast, Ekmekci et al (2004) reported methylation in 61% of AML patients.…”
Section: Dna Hypermethylation Of Cell Cycle and Apoptotic Genes In Pementioning
confidence: 75%
See 2 more Smart Citations
“…7,11 The mechanism by which FAS promoter is overmethylated in sAML is still unclear. However, the 5 0 -CpG1-8 are located immediately downstream of the docking site of Dnmt1, which promotes FAS promoter methylation in KRAS-transformed NIH3T3 cells.…”
Section: Letters To the Editormentioning
confidence: 99%